ROLES OF HYDRAULIC PARAMETERS IN DELINEATION OF AQUIFER PROTECTIVE ZONES AND SOIL CORROSIVITY IN KALTUNGO AND ENVIRONS, NORTH-EASTERN, NIGERIA - S. MUKKAFA; I.A KWAMI; A.I HARUNA; A.M INUWA; S. SALEH; N.A MUSTAPHA; A.D. UMAR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The aquifer protective capacity and corrosivity of near surface materials in Kaltungo and environs was evaluated using Electrical resistivity method. Thirty-five Vertical Electrical Soundings (VES) stations were employed using Schlumberger configuration. The result indicates Five geoelectric layers with varying thicknesses and resistivities. Layers four and five are the likely aquiferous horizons with resistivities 47.4Sm. The depth to the aquiferous horizon wideranging between 7.3m-92.0m, and has a rather irregular distribution and thicknesses. Corrosivity, and longitudinal unit conductance (S) maps were generated from the combination of first and second order geoelectric parameters. The results indicate that the Kofar Sarki, Baganje and Okra areas are characterized by poor protective capacity; Karel, Ledeben and Popandi areas are characterized by weak protective capacity (0.1-0.2 mhos) while other locations investigated are underlain by materials which could be regarded as moderate (0.2-0.69 mhos) to good (0.7-4.9 mhos) protective capacity. Resistivity values within the first layer (8.0-141.3 Sm) indicate that this layer is moderately aggressive and may likely form corrosion which may lead to significant corrosion failures of shallow subsurface installation facilities. The results of this research highlight certain environmental factors (corrosivity and protective capacity) that should be considered at the planning stages of residential estates.